Electron accelerator for energy up to 5.0 MeV and beam power up to 50 kW with Х-ray converter - Auslender, V.L.; Bryazgin, A.A.; Cheskidov, V.G.; Gornakov, I.V.; Kokin, E.N.; Kuznetsov, G.I.; Lukin, A.N.; Makarov, I.G.; Maximov, S. A.; Nekhaev, V.E.; Ostreiko, G.N.; Panfilov, A.D.; et al. (Вопросы атомной науки и техники, 2004)
The paper describes the industrial electron accelerator ILU-10 for electron energy up to 5 MeV and beam power up to 50 kW specially designed for use in industrial applications. The ILU-10 accelerator generates the vertical electron beam. The beam line turns the beam through an angle of 90° and transports the beam to the vertically posed Xray converter to generate the horizontal beam of X-rays. Приводиться опис прискорювача електронів ІЛУ-10 на енергію 5 МеВ потужністю 50 кВт, спеціально розробленого для таких комплексів. Для спрощення конструкції конвеєрної системи подачі оброблюваної продукції в зону опромінення використовується випускний пристрій з поворотом пучка на 90 градусів інаступною конвертацією електронного пучка в гамма-випромінювання на вертикально розташованій мішені. Приводится описание ускорителя электронов ИЛУ-10 на энергию 5 МэВ мощностью 50 кВт, специально разработанного для таких комплексов. Для упрощения конструкции конвейерной системы подачи обрабатываемой продукции в зону облучения используется выпускное устройство с поворотом пучка на 90 градусов и последующей конвертацией электронного пучка в гамма-излучение на вертикально расположенной мишени.